2016
DOI: 10.1108/ajems-02-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of agricultural productivity growth in Africa

Abstract: Purpose The purpose of this paper is to decompose total factor productivity (TFP) changes of the agriculture sector in ten African countries. Design/methodology/approach A fixed-effects estimation is applied to estimate the translog production function. Findings The study results are consistent with previous studies, indicating low TFP. Furthermore, of the TFP components, only technical change (TC) is positive. This study proposes that credit be made available to farmers in Egypt, Morocco, Algeria, and Tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Third, recent agricultural literature on agro-allied industrialization for development in Africa has largely focused on inter alia: the effect of irrigation on food production (Nonvide, 2017); improving productivity via warehousing systems (Katunze et al, 2017); gender differences among subsistence farmers and the willingness to undertake agribusiness (Coker et al, 2017); the role of the female farmer entrepreneurs in poverty reduction (Nukpeza and Blankson, 2017); multinationals in Africa's food retail businesses (Nandonde and Kuada, 2017); transmission of international food prices (or imported inflation)to African markets (Furceri et al 2016;van Weezel, S., 2016;Fiamohe et al, 2015); the role of value chains in agricultural business (Ndyetabula et al, 2016) and the composition of agricultural productivity (Mohamed et al, 2016). Noticeably missing is that the literature on the nexus between foreign aid and agriculture has not assessed whether ODA for agriculture and rural development is relevant in increasing productivity in agriculture.…”
Section: Theoretical Highlights and Brief Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Third, recent agricultural literature on agro-allied industrialization for development in Africa has largely focused on inter alia: the effect of irrigation on food production (Nonvide, 2017); improving productivity via warehousing systems (Katunze et al, 2017); gender differences among subsistence farmers and the willingness to undertake agribusiness (Coker et al, 2017); the role of the female farmer entrepreneurs in poverty reduction (Nukpeza and Blankson, 2017); multinationals in Africa's food retail businesses (Nandonde and Kuada, 2017); transmission of international food prices (or imported inflation)to African markets (Furceri et al 2016;van Weezel, S., 2016;Fiamohe et al, 2015); the role of value chains in agricultural business (Ndyetabula et al, 2016) and the composition of agricultural productivity (Mohamed et al, 2016). Noticeably missing is that the literature on the nexus between foreign aid and agriculture has not assessed whether ODA for agriculture and rural development is relevant in increasing productivity in agriculture.…”
Section: Theoretical Highlights and Brief Literaturementioning
confidence: 99%
“…The effectiveness of development aid (Nandonde and Kuada, 2017); transmission of international food prices (or imported inflation) to African markets (Furceri et al 2016;Van Weezel, 2016;Fiamohe et al, 2015); the role of value chains in agricultural business (Ndyetabula et al, 2016) and the composition of agricultural productivity (Mohamed et al, 2016). Noticeably, missing is that the literature on the nexus between foreign aid and agriculture has not assessed whether ODA for agriculture and rural development is relevant in increasing productivity in agriculture.…”
mentioning
confidence: 99%
“…However, the study also found that sectors and/or subsectors that were primarily dependent on domestic demand did not perform to the best of their potential, although technological change had a positive impact on the sectors' growth performance. Similarly, Mohamed et al (2016) decomposed TFP changes in the agriculture sector in ten African countries by using a panel data set for 1980-2008, with a fixed effects model applied to a translog production function. The results of the study supported the claim that the agricultural sector in these ten African economies had low TFP-a result already established in the literaturebut technological change had a positive impact on the growth of the sector, leading to the suggestion that credit should be made available to farmers as part of the agricultural development programme in the region, to improve TFP.…”
Section: Review On the South African Economymentioning
confidence: 99%
“…This study proposes that credit should be made available to farmers in Egypt, Morocco, Algeria and Tunisia. Furthermore, agricultural development programs should be implemented in South Africa and Senegal to improve the productivity in these countries (Mohamed et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%